Effect of treatment process on the formability of Fe–Al alloy powders and the crushing strength of green compacts - DENG Ying; WU Yin-jiang; NAN Hai-juan; LIANG Yong-ren; MENG Qiang (Fenmo yejin jishu)
To improve the formability of Fe–Al alloy powders and the crushing strength of green compacts, the effects of hydrogen reduction and vacuum annealing on the morphology and properties of the Fe–Al alloy powders were analyzed, and the forming rate of the tube billets made from the original powders and the treated powders were studied. The results show that, after the hydrogen reduction and vacuum anneal treatment, the morphology of the original Fe–Al alloy powders has little change, the powder properties are enhanced, and the crushing strength and formability of the green compacts are improved. Especially after the vacuum anneal treatment, the powder properties are significantly enhanced, oxygen mass fraction decrease from 0.5% to 0.2%, apparent density decrease from 1.82 g·cm−3 to 1.64 g·cm−3, microhardness decrease from HV 260 to HV 158, compression ratio decrease from 63% to 56%, crushing strength of the green compact increase from 2.0 MPa to 2.7 MPa, the formability is greatly improved. In the quantity production of long tube billets, the vacuum annealing pretreatment of the original Fe–Al alloy powders can effectively increase the qualified rate of the long tube billets from 50% to 100% and reduce the product cost.